KEGIATAN ANALISIS BEBAN KERJA DI PT. BOSOWA BERLIAN MOTOR MAKASSAR - Tetteng, Basti; Mangarengi, Yusyah Alreffyanny; Cahyani, Indah; Ramadhani, Indri; Saputri, Sri Dewi; Rahmah, Tri (Devote: Jurnal Pengabdian Masyarakat Global, 2022)
Workload analysis is a technique that performs to calculate the workload of employees in a company. Workload analysis aims to help PT. Bosowa Berlian Motor in the adjustment of the efficiency of human resources (HR). The method used in this study is the guided free-type interview method. This method makes it easier for the interviewee to freely ask questions to the interviewer regarding workload or in terms of career development at the company. Data analysis techniques were carried out using FTE (Full Time Equivalent) calculations through software in Microsoft Excel. The results of workload analysis by using FTE calculations that are classified as FIT in the mechanical position of Mechanic are CS ASS, Sales Spare Parts, and Cashier. The results that are classified as FIT are not given the recommendation to do a Job Redesign. In addition, the result of the FTE showed that there some positions are classified as Under Fit, CS, SalesForce, Accounting Staff, and Sales Advisor. The result of the FTE which was categorized as overload are ASS admin and talent management and org development.